Dermal macrophages control tactile perception under physiological conditions via NGF signaling - Tatsuhide Tanaka; Ayami Isonishi; Mitsuko Banja; Rikuto Yamamoto; Masaki Sonobe; Emiko Okuda-Ashitaka; Hidemasa Furue; Hiroaki Okuda; Kouko Tatsumi; Akio Wanaka (Scientific Reports)
Abstract We demonstrated previously that sorting nexin 25 (SNX25) in nerve-associated macrophages plays critical roles in pain sensation by regulating tissue NGF content under both physiological and neuropathic conditions. In the present study, we apply the SNX25–NGF paradigm to tactile perception by showing that Snx25 +/- mice or macrophage-specific Snx25 conditional knock-out (mcKO) mice had weaker responses to tactile stimuli in normal conditions. Snx25 mcKO mice responded poorly to transcutaneous electrical stimuli at a frequency of 5 Hz (C fiber responses), but normally to stimuli at a frequency of 250 Hz (Aδ fiber responses) or of 2000 Hz (Aβ fiber responses). CX3CR1-positive dermal macrophages were frequently found near calcitonin gene–related peptide (CGRP)- positive nerves and, less frequently, tyrosine hydroxylase (TH)-positive nerves. We confirmed that the tissue content of NGF was lower in Snx25 mcKO mice than in wild-type mice, and in turn, dermal NGF injection restored tactile sensitivity in Snx25 +/- mice and Snx25 mcKO mice to normal levels. These results indicate that CGRP-positive C-nociceptors (possibly also TH-positive C-LTMRs) associated dermal macrophages control tactile perception by producing NGF and secreting it into the dermis.